ANALYSIS OF THE USE OF THE FRAUD HEXAGON MODEL IN DETECTING FRAUD IN STATE-OWNED ENTERPRISES IN INDONESIA - Mawardi, Rizal; Soimah, Soimah; Shaliha, Karrin Aulia; Septian, Wahyu Eka; Haron, Rosmawati (Jurnal Akuntansi Bisnis, 2026)
Background: State-owned enterprises (SOEs) face unique fraud vulnerabilities due to institutional complexity and dual accountability. The 2019 ACFE Indonesia Survey revealed SOEs ranked second among institutions most harmed by fraud (31.8%). High-profile cases demonstrate the severity of this governance challenge. Existing fraud frameworks inadequately address the multi-layered risk environment characteristic of state ownership structures. Objective: his study examines fraud hexagon model adequately captures fraud dynamics in Indonesian SOEs by testing how six elements stimulus, capability, collusion, opportunity, rationalization, and ego influence financial statement fraud while accounting for institutional peculiarities of state ownership. Research Methods: Using purposive sampling, 16 SOEs listed on the Indonesia Stock Exchange (2017-2022) provided 96 firm-year observations. Financial statement fraud is measured using the F-score model (Dechow et al., 2011). Independent variables operationalize fraud hexagon elements: stimulus (ROA), capability (CEO education), collusion (price-to-book ratio), opportunity (receivables-to-sales changes), rationalization (auditor changes), and ego (managerial ownership). Multiple regression analysis using EViews 13 tests hypotheses at 5% significance. Research Results: Three elements significantly influence fraud: financial targets, nature of industry, and managerial ownership. CEO education, market performance, and auditor changes show no significant effects, suggesting individual characteristics matter less in institutionally-determined fraud environments. Originality/Novelty of Research: This study proposes an "Institutional Fraud Framework" recognizing that fraud hexagon elements operate differently in SOE contexts—some amplified, some neutralized, and some reversed. It represents the first comprehensive test of all six elements in Indonesian SOEs, using F-score continuous measures for nuanced fraud detection. Findings demonstrate the need for context-specific fraud theories rather than universal private sector models.